Micro, Small And Medium Enterprises Strategies of Getuk Nyimut in Market Challenges - Mira Meilia Marka (The Graduate School of Sahid University, 2022)
MSMEs of Getuk Nyimut contributed to the economy of the society around Kajar village, Kudus Regency. Competition of MSMEs grew along with the number of new businesses. Entrepreneurs getuk nyimut attracted consumers with the products and services. MSMEs give some facilities to the outlets such as wifi and music. It could be innovation strategies to improving business. Getuk Nyimut’s Entrepreneur need to increase their ability to innovate and create marketing performance. This capability could be built through increasing social capital and human capital. This study aimed to solve the inconsistencies of previous research. The research data source was primary data from questionnaires filled out by respondents. The research sample was 31 getuk nyimut’s entrepreneurs located in Kajar Village. This study used the Structural Equation Modeling analysis technique with the PLS program. The result of this research showed that Social Capital has a positive and significant effect on Inovation Capability, Human Capital has a positive and significant effect on Inovation Capability, Social Capital has no effect on Marketing Performance, Human Capital has insignificant effect on Marketing Performance, Inovation Capability has insignificant effect on Marketing Performance. ABSTRAK UMKM Getuk Nyimut memberi kontribusi kepada perekonomian masyarakat sekitar desa Kajar Kabupaten Kudus. Persaingan UMKM getuk nyimut mulai tumbuh seiring dengan banyaknya usaha yang berdiri. Pengusaha getuk nyimut menarik konsumen melalui produk dan layanan yang diberikan. Fasilitas yang ditambahkan pada gerai adalah dengan melengkapi wifi dan musik. Hal tersebut menjadi salah satu strategi inovasi UMKM dalam meningkatkan usaha. Pemilik UMKM perlu meningkatkan kemampuan inovasi untuk menciptakan kinerja pemasaran. Kemampuan tersebut dapat dibangun melalui peningkatan modal social dan human capital. Penelitian ini bertujuan untuk memberikan kontribusi adanya inkonsitensi penelitian sebelumnya. Sumber data penelitian merupakan data primer yang berbentuk kuesioner dari responden penelitian. Sampel penelitian adalah 31 pengusaha getuk nyimut yang berlokasi di Desa Kajar. Analisis data yang digunakan dalam penelitian adalah Structural Equation Modeling melalui program PLS. Hasil penelitian yaitu Social Capital memiliki pengaruh positif dan signfikan terhadap Inovation Capability , Human Capital berpengaruh positif dan signfikan terhadap Inovation Capability, Social Capital tidak berpengaruh signifikan terhadap Marketing Performance, Human Capital tidak berpengaruh signifikan terhadap Marketing Performance, Inovation Capaility tidak berpengaruh signifikan terhadap Marketing Performance.Kata Kunci : Modal Sosial, Modal Manusia, Kemampuan Inovasi, Kinerja Pemasaran.